Análise da influência dos parâmetros na deposição por aspersão térmica HVOF de revestimentos resistentes à cavitação - Alcover Junior, Paulo Roberto Campos (2014)
Erosion by cavitation is the best problem in hydraulic turbines that lead to new studies about recovery and maintenance of the original profile. Many stainless alloys are used in order to provide more resistance to this phenomenon, as well as the development of deposition processes. But currently use methods such as deposition by thermal spray ASP, usually followed by remelting the PTA Plasma aiming at relieving residual stresses generated by sprinkling, MIG / MAG welding is also used for the same purpose, this generates tensions with greater magnitude that sprinkling, as well as the presence of microcracks, thus impairing the life of the machine, generating costs of maintenance and repair and can lead to catastrophic results. Trying to minimize the effects of residual stresses and contribute to increased component life, cavitation resistant coatings are being developed and deposited on turbine blades by other processes such as thermal spraying HVOF (High Velocity Oxygen Fuel), Dispensing later remelt the coating and provide increased grip, smaller amounts of oxides and pores as well as residual stresses minimized the magnitude and uniformity of the coating profile. Fe-Mn-Si-Cr steels are a class cavitation resistant, since they have to form a martensitic microstructure from deformation, thereby increasing the resistance against cavitation during the occurrence of the phenomenon that generates the surface hardening of the coating. The objective of this work is to analyze how the parameters used influence the mechanical properties of coatings Fe-Mn-Cr-Si with the addition of nickel and boron deposited by HVOF thermal spray on a substrate of Steel-C. The methodology used was experimental, where the coatings were deposited by thermal spray and varying parameters, torch distance to the substrate feed rate of the metal powder and pressure of the carrier gas, its mechanical properties were evaluated by means of techniques such as optical microscopy, scanning electron microscopy, microhardness testing and finally test accelerated cavitation. The results show some peculiarities among some parameters used together with certain characteristics of sprayed coating, for the alloys,the alloy with boron addition showed a higher content of oxides as well as porosity, but gave the largest coating hardness and resistance to cavitation.